Pengaruh Penerapan Disiplin Kerja dan Pelatihan Kerja Dalam Meningkatkan Produktivitas Kerja Karyawan di Departemen Produksi PT. MAS SUMBIRI Semarang - Sri Sulistyaningsih (LPPM STIE Anindyaguna, 2019)
The performance of a company is inseparable from the performance of an employee. The purpose of this study is to see how big the role of work discipline and job training on employee productivity. The data of this study used a questionnaire with a scale of 1-10 with the number of respondents being 57 employees. The sampling technique uses the census or parameter method which takes all respondents from employees who work in the production department. The data obtained were then analyzed using the SPSS 21 program. The results of this study confirm that the application of work discipline and job training can increase employee productivity in the company. Job training dominates in increasing employee productivity.